Social Psychological and Cultural Resilience in Its Influence on Exclusive Breastfeeding Behavior - Mohammad Dwinanda Junaedi; Titi Maharrani; Fatimah Zahra; Shawn Walker (International Journal of Advanced Health Science and Technology, 2024)
ABSTRACT Mother's milk (ASI) is the best food for babies that cannot be replaced by anything. Breastfeeding has been proven to be beneficial for both the baby and the mother. However, the coverage rate for achieving exclusive breastfeeding is still far below the target. This research aims to determine the influence of social psychological and socio-cultural resilience on exclusive breastfeeding behavior. This research is an analytical study with a cross sectional design. The sample in this study was 108 postpartum mothers taken using a simple random sampling technique. The independent variables in this research are social psychological and socio-cultural resilience, while the dependent variable is the behavior of postpartum mothers in providing exclusive breastfeeding. Data collection in this study used a questionnaire and was analyzed bivariately using the Chi Square and Fisher Exact Tests, while multivariate analysis used the Logistic Regression Test. The results of analysis using the Chi Square and/or Fisher Exact tests showed a p value > 0.05 for all indicators of social psychological resilience, which means that there are no indicators in this dimension that have an influence on exclusive breastfeeding. Meanwhile, for the socio-cultural resilience variable, the result was a p value of 0.014 or p value <0.05 on the social care indicator, which means that social care has a significant influence on exclusive breastfeeding. So it can be concluded that social psychological resilience has no effect on exclusive breastfeeding, while socio-cultural resilience influences exclusive breastfeeding on indicators of social concern.